The Discounted Money Value of Human Life Losses Associated With COVID-19 in Mauritius - Musango, Laurent; Nundoochan, Ajoy; Kirigia, Joses Muthuri (Frontiers in Public Health, 2020)
Background: Mauritius along with other 12 countries in the African Region was identified at the early start of the COVID-19 pandemic as being at high risk due to high volume of international travel, high prevalence of non-communicable diseases and co-morbidities, high population density and significant share of population over 60 years (16%). The objective of this study was to estimate the total discounted money value of human life losses (TDMVCLMAURITIUS) associated with COVID-19 in Mauritius. Methods: The human capital approach (HCA) was used to estimate the TDMVCLMAURITIUS of the 10 human life losses linked with COVID-19 in Mauritius as of 16 October 2020. The HCA model was estimated with the national life expectancy of 75.51 years and a discount rate of 3%. A sensitivity analysis was performed assuming (a) 5 and 10% discount rates, and (b) the average world life expectancy of 73.2 years, and the world highest life expectancy of 88.17 years. Results: The money value of human lives lost to COVID-19, at a discounted rate of 3%, had an estimated TDMVCLMAURITIUS of Int 3,120,689, and an average of Int 312,069 per human life lost. Approximately 74% of the TDMVCLMAURITIUS accrued to persons aged between 20 and 59 years. Reanalysis of the model with 5 and 10% discount rates, holding national life expectancy constant, reduced the TDMVCLMAURITIUS by 19.0 and 45.5%, respectively. Application of the average world life expectancy at 3% discount rate reduced TDMVCLMAURITIUS by 13%; and use of the world highest life expectancy at 3% discount rate increased TDMVCLMAURITIUS by 50%. Conclusions: The average discounted money value per human life loss associated with COVID-19 is 12-fold the per capita GDP for Mauritius. All measures implemented to prevent widespread community transmission of COVID-19 may have saved the country 837 human lives worth Int258,080,991. This evidence, conjointly with human rights arguments, calls for increased investments to bridge the existing gaps for achieving universal health coverage by 2030.